Research Performance of Lithium-Ion Battery for Off-Grid Solar System - Mohd Yaacob, Muhammad Zulhilmie (Progress in Engineering Application and Technology, 2023)
The purpose of this project is to find out more about the performance of lithium-ion for the system. The ability of lithium-ion (Li-ion) batteries to be the primary energy storage in off-grid renewable energy is presented.